PARTISIPASI MASYARAKAT DALAM PILKADES TAHUN 2013 (Penelitian Di Desa Batursari, Kecamatan Mranggen, Kabupaten Demak ) - Iwan Nuryanto; Purwoko .; Nunik Retno Wati (Journal of Politic and Government Studies, 2014)
ABSTRACTVillage elections for villagers is an important vehicle for them, because their fate is determined ahead of their chosen leader directly. Therefore, the villagers always expect the leader or head of the village who can lead well for the future. Political participation of the community is vital in a democracy. In the broad sense of political participation is citizen involvement in all stages of the policy, ranging from the time of making a decision until the assessment decisions, including the opportunity to participate in the implementation of the decision. The research method used in this study the quantitative research method is a systematic scientific research on the parts and phenomena and their relationships, which aims to develop and use mathematical models, theories, and hypotheses are mutually linked.In Batursari Village Head Election 2013, the participation of rural communities Batursari very high. This is not out of any money that is used as a political motivation in choosing the head of the village community. Political money itself has become a cultural village Batursari. Culture of money politics can not be separated from poverty, mentality, and culture of the village head is seen sorting event in getting the additional money. This suggests that the influence of money politics.Batursari rural community participation in Pilkades in 2013 Based on the study the majority of people make their choice by measuring the amount of value for money provided by the village head candidate. Not seeing the vision, mission and capabilities of the prospective head of the village. Of what is happening in the village Batursari Pilkades implementation in 2013 could be argued that the politics of education received by today's society is still lacking, especially for those in the middle to lower economic level. Political education from an early age is also intended to form the next generation intelligent in politics.Keywords: Public Participation, Village Head Election, Political Money